Ce que les transitions forestières font à l’expérience paysagère - Sébastien Nageleisen; Baptiste Hautdidier; Laurent Couderchet; Zoé Ginter (Projets de Paysage)
This paper investigates the complexity and diversity of landscape contexts and associated tree canopy dynamics. We use the example of wooded areas dominated by the Robinia pseudoacia in the Sauternes region of France. Introduced in France in the 17th century, the expansion of the species, although diffuse and unobtrusive, has nonetheless been rapid and spectacular. In order to apprehend the diversity of landscapes associated with Robinia groves, we highlight the various inconsistencies between the recent socio-ecological dynamics of the groves and their official recognition via classical methods of mapping and listing, either from above or below the forest canopy. The proposed combination of approaches (spatial analyses and photographic surveys, supplemented by interviews and archival sources) offers a more detailed interpretation of the modalities of these forest transitions and the contradictory assessments of the landscapes associated with the “acacia”, largely overlooked in public initiatives.